Socioeconomic differentials of the members of BRAC Gonokendra Patltagar - Khan, Md. Kaisar A (Research and Evaluation Division, Brac, 2019)
This study aimed to document the socioeconomic background of the members of BRAC Gonokendra (community-based library). to identify why some members did not avail its services and why some members of the Management Committee did not play an active role in managing the pathagars. A total of 904 members were selected through systematic random sampling. Besides, 74 general users and 26 members of the Management Committee were selected purposively. The study revealed that the programme successfully mobilised the literate rural people of all age groups as well as all economic strata. More male members attended than female members, but female members borrowed more books than male members. Children and students of lower grades were more regular in attendance and borrowed more books than members of higher age groups and the students of higher grades. Amongst the non-student members, the higher educated were more regular in attendance than the lower educated, and borrowed more books. Lack of interest of the members towards pathagars, lack of reading habit, students' tum over from the associated schools or colleges, lack of new arrivals of reading materials, and pressure of academic study seemed to be the major reasons for not availing the services of the pathagars. On the other hand, members of the Management Committee did not play an active role due to dependency on BRAC staff, lack of practice of power, and involvement in occupational activities. It was realised that there still have rooms to extend its services among the target population. Thus, extensive campaigns are needed to motivate the members as well as the community to maximize the use of pathagars. At the same time, a participatory management system may be applied to ensure more close community involvement in managing the pathagars.